2014
DOI: 10.3892/or.2014.2972
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SEMA3B methylation and expression patterns in gastric cancer tissue and cell lines

Abstract: Abstract. The family of semaphorins has been demonstrated to possess tumor suppressor activity, in which semaphorin 3B (SEMA3B) is differentially expressed in several types of tumors. The relationship between SEMA3B expression and its clinical significance in gastric cancer (GC) is currently unclear. In the present study, the expression and methylation status of the SEMA3B gene were detected by quantitative PCR and bisulfite sequencing PCR (BSP). Data indicated that the levels of SEMA3B mRNA decreased in gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Hypermethylation often reduces the mRNA levels not only of SEMA3B but also of some other genes of the LUCA region in tumors; e.g., RASSF1A , BLU , and CACNA2D2 [ 36 38 ]. SEMA3B methylation has been observed in various types of cancer, including lung, liver, gallbladder, gastric, breast and oral carcinomas, and neuroblastoma [ 17 , 54 61 ]. However, these studies included only the CpG-island, which, according to the NCBI database ( http://www.ncbi.nlm.nih.gov/ ), belongs to the first intron (+1350..+1700 bp from SEMA3B 5’-end) of SEMA3B .…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation often reduces the mRNA levels not only of SEMA3B but also of some other genes of the LUCA region in tumors; e.g., RASSF1A , BLU , and CACNA2D2 [ 36 38 ]. SEMA3B methylation has been observed in various types of cancer, including lung, liver, gallbladder, gastric, breast and oral carcinomas, and neuroblastoma [ 17 , 54 61 ]. However, these studies included only the CpG-island, which, according to the NCBI database ( http://www.ncbi.nlm.nih.gov/ ), belongs to the first intron (+1350..+1700 bp from SEMA3B 5’-end) of SEMA3B .…”
Section: Discussionmentioning
confidence: 99%
“…143,144 Sema3B:The sema3B gene was identified along with sema3F as a tumor suppressor gene whose function is lost in small cell lung carcinoma cells by a variety of mechanisms that include promoter methylation and loss of heterozygosity. 91,[145][146][147][148][149][150] Sema3B also functions as an endogenous inhibitor of endometrial cancer, 151 and in oral squamous cell carcinoma in which its expression is inhibited as a result of promoter methylation. 152 In agreement with these observations single nucleotide polymorphisms in the sema3B gene were also found to be associated with poor prognosis of prostate cancer.…”
Section: Semaphorins As Regulators Of Tumor Progressionmentioning
confidence: 99%
“…It is necessary to study the roles of other TSGs at this region in GCA tumorigenesis. Semaphorin 3B (SEMA3B), located on 3p21.3, is frequently inactivated in several types of carcinomas [11][12][13][14][15]. SEMA3, the only secreted soluble molecules of semaphorins family, was first identified as glycoproteins that negatively mediate neuronal guidance by binding to neuropilin and repelling neurons away from the source of SEMA3 [16].…”
Section: Introductionmentioning
confidence: 99%
“…The following studies have demonstrated that SEMA3B play inhibitory roles in tumor proliferation and angiogenesis [17]. Moreover, like other TSGs located at 3p21.3, the inactivation of SEMA3B in tumors may be caused by multiple mechanisms including allelic loss and aberrant CpG site methylation [11,14,15,[18][19][20]. However, the critical CpG sites and exact roles of SEMA3B in GCA have not been clarified.…”
Section: Introductionmentioning
confidence: 99%